Relational resiliences: reflections from pastoralism across the world - Greta Semplici; L. Jamila Haider; Ryan Unks; Tahira S. Mohamed; Giulia Simula; Palden Tsering (Huadancairang); Natasha Maru; Linda Pappagallo; Masresha Taye (Ecosystems and People)
Resilience is a common concept in pastoralism scholarship and policy-making, especially in dryland environments where livelihoods are considered vulnerable to frequent shocks such as droughts, pests and epidemics, and conflicts. Resilience lends itself to pastoral studies due to its ability to capture uncertainty, complexity and dynamism: key characteristics of dryland environments and pastoral systems. However, resilience has also been critiqued for inadequately incorporating aspects of power, its emphasis on individual agency and nature-culture dualism, and its problematic application in development. We build on recent sociology, anthropology, and scholarship on pastoralism to contribute to the ‘relational turn’ in sustainability science to address: How can an approach focused on processes and relations, and socio-ecological interdependence help us better understand resilience in pastoral landscapes? And vice versa: how can pastoralism offer insights about how to understand resilience starting from processes and relations? We compare different empirically grounded formulations of resilience that researchers operationalize in six pastoral case studies from Africa, Asia and Europe.